Thermoelectric generator electrical performance based on temperature of thermoelectric materials - Parveen, S; Victor Vedanayakam, S; Padma Suvarna, R (International Journal of Engineering and Technology, 2018)
In space applications, the radioisotope thermoelectric generators are being used for the power generation. The energy storage devices like fuel cells, solar cells cannot function in remote areas, in such cases the power generating systems can work successfully for generating electrical power in space missions. The efficiency of thermo electric generators is around 5% to 8% . Bismuth telluride has high electrical conductivity (1.1 x 105S.m /m2) and very low thermal conductivity (1.20 W/ m.K). A Thermoelectric generator has been built up consisting of a Bi2Te3 based on thermoelectric module. The main aim of this is when four thermoelectric modules are connected in series, the power and efficiency was calculated. The thermoelectric module used is TEP1-1264-1.5. This thermoelectric module is having a size of 40mmx40mm. The hot side maximum temperature was 1600C where the cold side temperature is at 400C. At load resistance, 15Ω the maximum efficiency calculated was 6.80%, at temperature of 1600C. The maximum power at this temperature was 15.01W, the output voltage is 16.5V, and the output current is 0.91A. The related and the corresponding graphs between efficiency, power, output voltage, output current was drawn at different temperatures. The efficiency of bismuth telluride, thermoelectric module is greater than other thermoelectric materials.
Keywords: Thermoelectric Power Generator; Thermoelectric Materials; Load Resistance; Efficiency.